PENINGKATAN KECERDASAN INTRAPERSONAL DAN KECERDASAN INTERPERSONAL MELALUI METODE BERMAIN PERAN DI KELOMPOK B PAUD TITIAN KASIH: IMPROVING INTRAPERSONAL INTELLIGENCE AND INTERPERSONAL INTELLIGENCE THROUGH ROLE PLAYING METHOD IN GROUP B OF TITIAN KASIH PAUD - Sahidun, Nurfitri; Ismail, Radjiman (Universitas Islam Malang, 2019)
The aims of this research to know the increased of children intrapersonal intelligence and interpersonal intelligence through role playing methods. Respondents of the research involved of 20 children from group B at PAUD Titian Kasih. The method of this research consists by Kemmis and Taggart model. The score of data were analyzed by using quantitative and qualitative approach. The results of data indicate that interpersonal intelligence and intrapersonal intelligence of children have increased, based on the first cycle, it can be seen that children's interpersonal intelligence and intrapersonal intelligence have increased by 10.37%, in the pre-test the average the class average was 41.33 or 46.96% and in the first cycle it became 46 or 57.33%. In the second cycle of interpersonal intelligence and intrapersonal intelligence of children has increased by 22.59%. In the second cycle the children obtained an average score of 64.47 or 79.92%. The conclusions are the score of interpersonal intelligence and intrapersonal intelligence of children increases from pre-research to first cycle and from first cycle to second cycle, the implementation of the role playing method in teaching and learning gives children the opportunity to explore various intelligence possessed by children, especially intelligence interpersonal intelligence and intrapersonal intelligence.Â